On the Salaries of the Members of the Bulgarian National Assembly and the State of Emergency - Mihaylova, Ekaterina (Yearbook of the Law Department, 2019)
In the paper under consideration is the issue of the salary of the members of the Bulgarian National Assembly as a part of the development of parliamentarism. The topic is firstly considered in a historical perspective, including the legal regulation in the various Bulgarian constitutions. The current legal regulation is analysed as well as the decision of the National Assembly taken during the state of emergency, according to which decision it is accepted not to pay salaries to the members of the National Assembly as well as to persons in the executive power in the context of whether this decision is in consistency with the norms of the Constitution or not.